Mindfulness and Metacognitive Beliefs as Predictors of Students' Coping Strategies in Learning Filipino - Peñaflorida, Greaza; Limpot, Marilou (Journal of Interdisciplinary Perspectives, 2025)
Learning Filipino as a subject has concerned college students, leading to academic stress due to a lack of proficiency in the subject. This implies the need to investigate factors that can mitigate academic stress in learning Filipino, as it directly affects their performance. This study aimed to identify the relationship between mindfulness and metacognitive beliefs as predictors of students’ coping strategies in learning Filipino. A quantitative descriptive-correlational design was utilized to investigate the relationship and influence of the independent variables on the dependent variable. The participants of the study were 200 college students from a private school selected through random sampling. The study used adapted questionnaires for data collection and employed mean, Pearson r, and regression analysis to interpret the data. The findings indicated that students exhibited a high level of mindfulness and metacognitive beliefs, suggesting that these traits are often present. In contrast, their coping strategies for learning Filipino were moderate, implying that these strategies were used occasionally. A significant relationship was found between mindfulness and metacognitive beliefs; however, no such relationship was observed between these variables and students' coping strategies. Moreover, mindfulness and metacognitive beliefs did not significantly affect students' coping strategies in learning Filipino, suggesting that they are not predictors of the dependent variable. Overall, the study found no strong evidence of a direct effect between mindfulness, metacognitive beliefs, and students' coping strategies. Considering these findings, further investigation into additional factors that may significantly influence coping strategies is recommended to address academic stress.